Low cord blood Foxp3/CD3γ mRNA ratios: a marker of increased risk for allergy development. Issue 1 (January 2015) - Bullens, D. M. A.; Seys, S.; Kasran, A.; Dilissen, E.; Dupont, L. J.; Ceuppens, J. L.
Summary Background Data from birth cohort studies suggest that increased cord blood total IgE and reduced cord blood regulatory T cells increase the risk of developing allergic sensitization and atopic dermatitis. Objective We here addressed whether serum total IgE and hen's egg‐specific IgE levels at birth and at age 1 year differed between healthy and allergic children in a Belgian birth cohort (FONIA). We furthermore studied whether these parameters as well as cord blood Foxp3/CD3γ mRNA levels might predict the allergic outcome. Methods and results Children (n = 84) were clinically assessed at the ages of 6, 12, 18, and 24 months and at 6 years. Cord blood total IgE levels above 0.35 kU/L predicted early (i.e. before or at the age of 2 years) allergy development. Presence of serum IgE antibodies to hen's egg (cut‐off 0.05 Ua/mL) at the age of 1 year was associated with early as well as late (i.e. between the age of 2 and 6 years) allergy development. Cord blood Foxp3/CD3γ mRNA ratios were significantly lower in early allergic children and levels below 0.32 predicted the allergic outcome. Conclusions and clinical Relevance Low cord blood Foxp3/CD3γ mRNA ratios are highly predictive for early allergy development, whereas specific IgE levels to hen's egg white above 0.05 Ua/mL at age 1 year predict allergy development in general.